Pelaksanaan Jamsostek Program Jaminan Pemeliharaan Kesehatan Bagi Pekerja / Buruh Di PT. Deta Sukses Makmur - Ferra Ika Wardani, Sonhaji *), Solechan (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Employers are required to engage its workforce in Jamsostek program must register with the company and labor / workers as participants of the employees' social security administrators with the form provided. For those who did not register, and after being given a warning obligation still not doing it will be sanctioned revocation in accordance with Article 47 point a PP No. 14 year 1973 regarding Social Security Program Operator.PT. Deta Sukses Makmur is a company engaged in outsourcing labor brokers. PT. Deta Sukses Makmur is including one company that must comply with regulations - regulations on jamsostek. Therefore, PT. Deta Sukses Makmur shall involve outsourcing workers in the Social Security program in particular Health Care Insurance.The research method used in this study is empirical legal research specifications and descriptive analytical sample method in the form of non-random sampling method. While the data analysis methods used are qualitative analysis.Based on the research turned out to PT. Deta Sukses Makmur has implemented programs in particular Social Security Health Insurance. Although in practice the obstacles or constraints but the obstacles or constraints can be solved properly by PT. Deta Sukses Makmur.